1992
DOI: 10.1149/1.2069479
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Breakdown and Current Conduction of Oxide/Nitride/Oxide Multi‐Layer Structures

Abstract: We present a detailed study on the effect of bottom-and top-oxide thicknesses on the current conduction and the dielectric breakdown of oxide/nitride/oxide (ONO) multi-layer dielectrics. An abrupt reduction in current is observed when the oxide that is contiguous to the anode is thicker than 3 nm. This leads us to conclude that the thick oxide (>3 nm) impedes hole injection from anode into nitride. The injected charge-to-breakdown (QBD) and the time-to-breakdown (TBD) are measured to study the breakdown mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…The ONO gate stack was formed in four major process steps: after a conventional pre-gate oxide clean, the silicon surface was first oxidized in oxygen at a pressure of 800 mtorr and a temperature of 750 C to form an oxide thickness of 10 Å. Twenty Å of silicon nitride was then deposited on the oxidized layer at a pressure of 100 mtorr and a temperature of 800 C using dichlorosilane and ammonia as deposition precursors. To establish an electrical contact with poly-si electrode [9] and suppress gate leakage current [17], the dual layer was then topped with a 10 Å Tetraethoxysilane (TEOS) oxide deposited at a pressure of 450 mtorr and a temperature of 700 C. The TEOS oxide is needed to suppress gate leakage current. The whole ONO stack was then in-situ densified in N O gases at the TEOS deposition temperature and then ex-situ annealed with a rapid thermal process (900 C for 30 s in nitrogen) which reduces SiO /Si interfacial defect density and fixed charge density [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ONO gate stack was formed in four major process steps: after a conventional pre-gate oxide clean, the silicon surface was first oxidized in oxygen at a pressure of 800 mtorr and a temperature of 750 C to form an oxide thickness of 10 Å. Twenty Å of silicon nitride was then deposited on the oxidized layer at a pressure of 100 mtorr and a temperature of 800 C using dichlorosilane and ammonia as deposition precursors. To establish an electrical contact with poly-si electrode [9] and suppress gate leakage current [17], the dual layer was then topped with a 10 Å Tetraethoxysilane (TEOS) oxide deposited at a pressure of 450 mtorr and a temperature of 700 C. The TEOS oxide is needed to suppress gate leakage current. The whole ONO stack was then in-situ densified in N O gases at the TEOS deposition temperature and then ex-situ annealed with a rapid thermal process (900 C for 30 s in nitrogen) which reduces SiO /Si interfacial defect density and fixed charge density [11].…”
Section: Methodsmentioning
confidence: 99%
“…3(b). The nitrogen at the interface is one of the reasons that the dielectric reliability is improved [17]. However, the amount of nitrogen is not high enough to reduce carrier mobility.…”
Section: Methodsmentioning
confidence: 99%
“…Nitride/oxide gate dielectrics have already been widely used [2][3]. Materials other than silicon nitride, while attractive from the dielectric constant viewpoint show additional problem.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of ionic conduction within the ONO layer is also of prime importance to the charge retention capability in the non-volatile memory devices. Several authors [1]-[3J have studied this ionic conduction in silicon nitride and ONO structures, and discussed their breakdown phenomena. K. Kobayashi etaL [1] presented a detailed discussion on the effect of the bottom-and top-oxide thickness on the current conduction and the dielectric breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…The constant current-stressing technique is a simple straight forward method to assess the integrity of the dielectric layer. For Flash devices, various authors [1,4,5] have shown that both electrons and holes can be easily injected from the polysilicon layers into the ONO dielectric layer, which is sandwiched between them. We strongly believe that any variations in the material properties of the polysilicon electrodes, especially those changes which can cause reductions in the carriers' flow through the polysilicon and oxides, or improve the conditions of the interfaces between the polysilicon layers and oxides, can constitute a substantial increase in the dielectric layer breakdown time [6].…”
Section: Introductionmentioning
confidence: 99%